Effects of livestock on the quality of the riparian forest, soil and water in Nothofagus silvopastoral systems - Gomez, Federico Antonio; Tarabini, Manuela Mabel; La Manna, Ludmila Andrea; Von Müller, Axel (Springer Nature, 2024)
Controversial aspects of production vs.conservation were profusely discussed globally by considering climate change and its impact on ecosystem services provision. However, previous meticulous livestock planning and short to medium-term ecosystem services monitoring make it compatible. This work aims to evaluate the effects of livestock on the quality of riparian forests, soil, and water in Nothofagus silvopastoral systems. Three river basins under livestock rearing were evaluated with different historic and actual stocking rates. Along three years, the physical, chemical, and bacteriological properties of soil, water, and quality of the riparian forest were evaluated. The basin without the presence of livestock showed the best quality of water and riparian forest. While the greater livestock stocking rate in riparian zones caused a deterioration of forest, decreasing the canopy cover, due to browsing and trampling of forest regeneration. In addition, livestock contributes faeces and urine into streams, producing the entry of sediment, nitrogen, phosphorus, and bacteria that negatively affect the quality of the water. The decrease of water quality is particularly accentuated in hot and dry years. However, Andean Patagonian streams and rivers have the capacity for self-purification of water with distances greater than 1,000 m without the presence of livestock, in which Escherichia coli disappears. On the other hand, sites with a higher livestock stocking rate, bare soil, and a lower degree of allophanization presented a greater turbidity in the water. To contribute to the goal of making silvopastoral systems production and ecosystem services supply compatible, we recommend livestock exclusion from the riparian zone, and keeping resilient areas under grazing with controlled stocking rates. Additionally, a monitoring program is necessary to prevent ecosystems from misfunctioning.